The role of the gut microbiome and microbial metabolism in mediating opioid-induced changes in the epigenome - Kolli, Udhghatri; Roy, Sabita (Frontiers in Microbiology, 2023)
The current opioid pandemic is a major public health crisis in the United States, affecting millions of people and imposing significant health and socioeconomic burdens. Preclinical and clinical research over the past few decades has delineated certain molecular mechanisms and identified various genetic, epigenetic, and environmental factors responsible for the pathophysiology and comorbidities associated with opioid use. Opioid use-induced epigenetic modifications have been identified as one of the important factors that mediate genetic changes in brain regions that control reward and drug-seeking behavior and are also implicated in the development of tolerance. Recently, it has been shown that opioid use results in microbial dysbiosis, leading to gut barrier disruption, which drives systemic inflammation, impacting the perception of pain, the development of analgesic tolerance, and behavioral outcomes. In this review, we highlight the potential role of microbiota and microbial metabolites in mediating the epigenetic modifications induced by opioid use.